Risk stratification and geographical mapping of Brazilian inflammatory bowel disease patients during the COVID-19 outbreak: Results from a nationwide survey - Queiroz, Natália Sousa Freitas; Teixeira, Fábio Vieira; Motta, Marina Pamponet; Chebli, Liliana Andrade; Hino, Adriano Akira Ferreira; de Almeida Martins, Camilla; Quaresma, Abel Botelho; de Paula da Silva, Alexandre Augusto; Damião, Adérson Omar Mourão Cintra; Saad-Hossne, Rogerio [UNESP]; Kotze, Paulo Gustavo (Baishideng Publishing Group, 2021)
BACKGROUND Coronavirus disease 2019 (COVID-19) pandemic is still evolving globally, and Brazil is currently one of the most affected countries. It is still debated whether patients with inflammatory bowel disease (IBD) are at a higher risk for developing COVID-19 or its complications. AIM To assess geographical distribution of IBD patients at the highest risk and correlate these data with COVID-19 mortality rates in Brazil. METHODS The Brazilian IBD Study Group (Grupo de Estudos da Doença Inflamatória Intestinal do Brasil) developed a web-based survey adapted from the British Society of Gastroenterology guidelines. The included categories were demographic data and inquiries related to risk factors for complications from COVID-19. Patients were categorized as highest, moderate or lowest individual risk. The Spearman correlation test was used to identify any association between highest risk and mortality rates for each state of the country. RESULTS A total of 3568 patients (65.3% females) were included. Most participants were from the southeastern and southern regions of Brazil, and 84.1% were using immunomodulators and/or biologics. Most patients (55.1%) were at moderate risk, 23.4% were at highest risk and 21.5% were at lowest risk of COVID-19 complications. No association between the proportion of IBD patients at highest risk for COVID-19 complications and higher mortality rates was identified in different Brazilian states (r = 0.146, P = 0.467). CONCLUSION This study indicates a distinct geographical distribution of IBD patients at highest risk for COVID-19 complications in different states of the country, which may reflect contrasting socioeconomic, educational and healthcare aspects. No association between high risk of IBD and COVID-related mortality rates was identified.
Keywords: Brazil; Colitis; COVID-19; Crohn's disease; Inflammatory bowel disease; Ulcerative